Confirmatory Factor Analysis of a 21st-Century Skills Instrument in Audiovisual-Assisted Problem-Based Learning - Setiawan, Hendrik; Nafiati, Dewi Amaliah; Munadi, Munadi (Jurnal Paedagogy, 2026)
This study aims to develop and validate a performance-based assessment instrument for measuring 21st-century skills in Ilmu Pengetahuan Alam dan Sosial (IPAS) learning through audiovisual-assisted Problem-Based Learning. The instrument comprises 16 essay items designed to assess four dimensions of the 4C framework—critical thinking, creativity, communication, and collaboration—with four items allocated to each dimension. Responses were scored using a 1–4 analytic rubric. An instrument development approach was employed, with construct validation conducted through a pilot test involving 30 sixth-grade students from SDN Brebes 10. Data were analyzed using Confirmatory Factor Analysis (CFA). The results indicate that all items are valid, with standardized factor loadings ranging from 0.897 to 0.967 (CR > 22.62; p < 0.001). The measurement model demonstrates excellent goodness-of-fit indices (χ² = 93.997; df = 98; p = 0.596; CFI = 1.000; TLI = 1.007; RMSEA = 0.000; SRMR = 0.023). All items exhibit very strong factor loadings (λ ≥ 0.80) and coefficients of determination (R²) ranging from 0.805 to 0.935. In addition, inter-factor correlations (–0.686 to 0.193) confirm adequate discriminant validity. Overall, these findings indicate that the developed instrument satisfies construct validity requirements and demonstrates excellent psychometric quality for assessing elementary students’ 21st-century skills in audiovisual-assisted IPAS learning.